THE IMPACT OF THE FILM WONDER WOMAN’S PRODUCTION ON CHANGING LGBT PERCEPTIONS IN INTERNATIONAL SOCIETY: A QUALITATIVE STUDY BASED ON CULTIVATION THEORY - Mufti Al Fariz, Abdul; Firdaus, Dwi Amanda; Prabuningtyas, Laksamana Juanda; Buana, Maulia Nabila Wahyu Nur; Ibrahim, Muhamad Dzaky Abdillah; Putri, Rizky Amelia (Journal of Media and Digital Society on SDGs, 2025)
This study aims to analyze the influence of the Wonder Woman film productions on changing public perceptions of the LGBT community abroad. Using a descriptive qualitative approach, the research applies George Gerbner’s Cultivation theory as the analytical framework to understand how media, especially films can shape social constructions of reality, including representations of gender and sexual orientation. Data were collected through direct observation of the films Wonder Woman (2017) and Wonder Woman 1984 (2020), as well as literature reviews from scholarly journals published within the last five years. The findings indicate that character portrayals and visual symbolism in the films provide interpretive spaces that reinforce representations of gender diversity and sexual orientation, impacting public perceptions of LGBT issues. Additionally, the study highlights the role of LGBT communities as agents of social change in advocating for human rights and equality, and emphasizes the importance of media in promoting diversity and fostering inclusivity in society. Keywords : Wonder Woman, LGBT Community, Cultivation theory, Gender Representation, Media.